Neuroimmunomodulatory and Neuroprotective Effects of the Flavonoid Apigenin in in vitro Models of Neuroinflammation Associated With Alzheimer’s Disease - Dourado, Naiara Silva; Souza, Cleide dos Santos; de Almeida, Monique Marylin Alves; Bispo da Silva, Alessandra; dos Santos, Balbino Lino; Silva, Victor Diogenes Amaral; De Assis, Adriano Martimbianco; da Silva, Jussemara Souza; Souza, Diogo Onofre; Costa, Maria de Fatima Dias; Butt, Arthur Morgan; Costa, Silvia Lima (Frontiers in Aging Neuroscience, 2020)
Neurodegenerative disorders (ND) are characterized by the progressive and irreversible loss of neurons. Alzheimer’s Disease (AD) is the most incident age-related ND, in which presence of a chronic inflammatory compound seems to be related to its pathogenesis. Different stimuli in the central nervous system can induce activation, proliferation and changes in phenotype and glial function, which can be modulated by anti-inflammatory agents. Apigenin (4,5,7–trihydroxyflavone) is a flavonoid found in abundance in many fruits and vegetables, that has shown important effects upon controlling inflammatory response. This study evaluated the neuroprotective and neuroimmunomodulatory potential of apigenin using in vitro models of neuroinflammation associated with AD. Co-cultures of neurons and glial cells were obtained from the cortex of newborn and embryonic Wistar rats. After 26 days in vitro, cultures were exposed to LPS (1µg/mL), or IL-1β (10ng/mL) for 24 h, or to Aβ oligomers (500nM) for 4 h, and then treated with apigenin (1µM) for further 24 h. It was observed that the treatment with apigenin preserved neurons and astrocytes integrity, determined by Rosenfeld’s staining and immunocytochemistry for β-tubulin III and GFAP, respectively. Moreover, it was observed by Fluoro-Jade-B and caspase-3 immunostaining that apigenin was not neurotoxic and has a neuroprotective effect against inflammatory damage. Additionaly, apigenin reduced microglial activation, characterized by inhibition of proliferation (BrdU+ cells) and modulation of microglia morphology (Iba-1+ cells), and decreased the expression of the M1 inflammatory marker CD68. Moreover, as determined by RT-qPCR, inflammatory stimuli induced by IL-1β increased the mRNA expression of IL-6, IL-1β and CCL5, and decreased the mRNA expression of IL-10. Contrary, after treatment with apigenin in inflammatory stimuli (IL-1β or LPS) there was a modulation of the mRNA expression of inflammatory cytokines, with increased expression of IL-10 and reduced expression of OX42, IL-6 and gp130. Moreover, apigenin alone and after inflammatory stimulus with IL-1β also induced the increase in the expression of brain derived neurotrophic factor, effect that may be associated with anti-inflammatory and neuroprotective effects. Together these data demonstrate that apigenin presents neuroprotective and anti-inflammatory effects in vitro and might represent an important neuroimmunomodulatory agent for the treatment of neurodegenerative conditions.